2016
DOI: 10.3171/2015.8.jns151624
|View full text |Cite|
|
Sign up to set email alerts
|

Hearing subclassification may predict long-term auditory outcomes after radiosurgery for vestibular schwannoma patients with good hearing

Abstract: OBJECTIVE In the era of MRI, vestibular schwannomas are often recognized when patients still have excellent hearing. Besides success in tumor control rate, hearing preservation is a main goal in any procedure for management of this population. The authors evaluated whether modified auditory subclassification prior to radiosurgery could predict long-term hearing outcome in this population. METHODS The authors reviewed a quality assessment registry that included the records of 1134 vestibular schwannoma patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…There are conflicting opinions regarding the use of a reference for hearing thresholds [8,41,42]. We employed the reference value of 40 dB HL because it has been used in other studies [8,15].…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting opinions regarding the use of a reference for hearing thresholds [8,41,42]. We employed the reference value of 40 dB HL because it has been used in other studies [8,15].…”
Section: Discussionmentioning
confidence: 99%
“…The latter group was further separated into whether the PTA in the affected ear was within 10 dB as compared with the contralateral ear (Class 1-B1 and Class 1-B2, respectively). 23 Following SRS, with a median follow-up of 65 months, serviceable hearing was preserved in Class 1-A, Class 1-B1, and Class 1-B2 patients in 98, 73, and 33%, respectively, and was significantly associated with the pretreatment GR class on multivariate analysis after controlling for age and gender. 23 Similarly, in a cohort of 77 VS patients, Kano and colleagues found that 71.4% of patients retained serviceable hearing with a median follow-up of 20 months after SRS and that GR Class 1 hearing before treatment was the only predictor for maintaining serviceable hearing.…”
Section: Patient Demographics and Pretreatment Hearing Levelsmentioning
confidence: 91%
“…23 Following SRS, with a median follow-up of 65 months, serviceable hearing was preserved in Class 1-A, Class 1-B1, and Class 1-B2 patients in 98, 73, and 33%, respectively, and was significantly associated with the pretreatment GR class on multivariate analysis after controlling for age and gender. 23 Similarly, in a cohort of 77 VS patients, Kano and colleagues found that 71.4% of patients retained serviceable hearing with a median follow-up of 20 months after SRS and that GR Class 1 hearing before treatment was the only predictor for maintaining serviceable hearing. 8 In a separate analysis, Hasegawa and colleagues reported on the outcomes of 117 VS patients with serviceable hearing treated with SRS utilizing a tumor margin dose of 12 Gy.…”
Section: Patient Demographics and Pretreatment Hearing Levelsmentioning
confidence: 91%
“…Serviceable hearing was preserved in only 23–24% patients at 10 years 4749 . Older age, larger tumors and poorer pre-treatment hearing were found to be risk factors for progressive post-treatment hearing loss 47,4950 . Reducing cochlear dose to improve hearing preservation continues to be controversial and has not been confirmed to reduce long-term hearing deterioration 51 .…”
Section: Radiation Therapymentioning
confidence: 99%